Effectiveness of Switching to Darunavir/Cobicistat in Virologically Suppressed HIV-Positive Patients Receiving Ritonavir-Boosted Protease Inhibitor–Based Regimen: The "STORE" Study. (1st July 2020) - Gori, Andrea; Antinori, Andrea; Vergori, Alessandra; Cossu, Maria Vittoria; Menzaghi, Barbara; Sterrantino, Gaetana; Rusconi, Stefano; Cattelan, Anna Maria; Castelli, Francesco; Gianotti, Nicola; Orofino, Giancarlo; Ripamonti, Diego; et al.
Abstract : Objective: This study investigates the effectiveness and tolerability of switching to a darunavir/cobicistat (DRV/c)-based antiretroviral regimen from a ritonavir-boosted protease inhibitor (PI/r)-based regimen in virologically suppressed HIV-positive patients. DRV trough values were also investigated. Setting: Prospective, multicenter, single-country, noninterventional cohort study. Methods: This study included patients on a PI/r-based ART for at least 12 months having plasma HIV-1 RNA <50 copies/mL since at least 6 months. The primary endpoint, defined as HIV-1 RNA <50 copies/mL, was measured at 48 ± 6 weeks from baseline. A secondary analysis was performed using the time to loss of virological response algorithm. Biochemical parameters, including DRV trough samples, were collected as per clinical practice and measured using high-performance liquid chromatography. Results: Of 336 patients enrolled, 282 completed the study: 70.8% had plasma HIV-1 RNA <50 copies/mL at 48 weeks; using the time to loss of virological response algorithm, 82.7% maintained virological suppression. Virological failure was observed in 6 patients (1.8%). Adverse event–related discontinuations were 4.5%. After 48 weeks, we found a significant improvement in both triglycerides (median, 130 to 113.5 mg/dL, P = 0.0254) and high-density lipoprotein cholesterol (48 to 49 mg/dL, P < 0.0001) but no change in other biomarkers. DRV trough concentrations in 56 subjects showed a median value of 2862.5 (1469.5–4439) ng/mL, higher in women than in men (4221 vs. 2634 ng/mL, P = 0.046). Conclusions: In stable HIV-1 positive virologically suppressed patients, the switch to DRV/c-based ART was beneficial in terms of low rates of virological failure and adverse events due to its high tolerability and improvement in triglycerides.